Biomarker-Driven Pharmacokinetics and Efficacy of Polymyxin B in Critically Ill Patients with XDR-GN Pneumonia - Wei Zuo; Qianlin Wang; Longxiang Su; Jiaxin Yu; Hongwei Fan; Qiang Fu; Yun Long; Bo Zhang (Pharmaceuticals)
Background: Achieving pharmacokinetic/pharmacodynamic (PK/PD) targets is critical for improving treatment success, particularly in critically ill patients. This study investigates the role of inflammatory biomarkers and their influence on the PK/PD characteristics of polymyxin B (PMB) in patients with extensively drug-resistant Gram-negative (XDR-GN) bacterial nosocomial pneumonia. Methods: Serial blood and/or bronchoalveolar lavage fluid (BALF) samples were collected at specified time points and analyzed for PMB and/or inflammatory biomarkers, including IL-6 and IL-10. Clinical data were also recorded, and their correlations with PK parameters were further analyzed. Results: Among the 27 enrolled patients, 22 (81.5%) achieved treatment success. The pharmacokinetic parameters of PMB included a maximum plasma concentration (Cmax) of 8.3 µg/mL, clearance (CL) of 1.55 L/h, volume of distribution (Vd) of 30.44 L, half-life (t1/2) of 19.56 h, steady-state area under the plasma concentration–time curve from time 0 to 24 h (AUCss,0–24h) of 110.08 h·µg/mL, and a plasma protein-binding ratio of 85.53%. The AUCss,0–24h metric was identified as a robust predictor of clinical efficacy, with an optimal cutoff value of 77.27 h·µg/mL. Notably, 48.15% of patients achieved the target AUCss,0–24h range of 50–100 h·µg/mL, with 76.95% of these patients attaining treatment success. Another 48.15% of patients exceeded this target, and 92.31% of this subgroup achieved treatment success. PMB demonstrated limited pulmonary penetration, with an epithelial lining fluid (ELF)/plasma ratio of 15.69% [16.86, 18.15]. Furthermore, TNF-α and the IL-6/IL-10 ratio were significantly correlated with PMB PK parameters. Conclusions: Our and others’ studies suggest heterogeneity of PMB PK parameters in critically ill patients. The majority of critically ill patients achieved or surpassed the recommended PK/PD targets and attained treatment success through intravenous administration of PMB at a simplified fixed dose. However, PMB did not achieve satisfactory pulmonary concentrations, suggesting that its efficacy may involve alternative mechanisms. The modulation of inflammatory responses may play a pivotal role in the treatment of severe infections, highlighting the potential for biomarker-guided therapeutic strategies.